Respiratory muscle training in healthy individuals: physiological rationale and implications for exercise performance - Sheel, A. W. (Sports Medicine, 2002)
The respiratory system has traditionally been viewed to be capable of meeting the substantial demands for ventilation and gas exchange and the cardiopulmonary interactions imposed by short-term maximum exercise or long-term endurance exercise. Recent studies suggest that specific respiratory muscle (RM) training can improve the endurance and strength of the respiratory muscles in healthy humans. The effects of RM training on exercise performance remains controversial. When whole-body exercise performance is evaluated using submaximal fixed work-rate tests, significant improvements are seen and smaller, but significant improvements have also been reported in placebo-trained individuals. When performance is measured using time-trial type performance measures versus fixed workload tests, performance is increased to a much lesser extent with RM training. It appears that RM training influences relevant measures of physical performance to a limited extent at most. Interpretation of the collective literature is difficult because most studies have utilised relatively small sample sizes and very few studies have used appropriate control or placebo groups. Mechanisms to explain the purported improvements in exercise performance remain largely unknown. However, possible candidates include improved ratings of breathing perception, delay of respiratory muscle fatigue, ventilatory efficiency, or blood-flow competition between respiratory and locomotor muscles. This review summarises the current literature on the physiology of RM training in healthy individuals and critically evaluates the possible implications for exercise performance.